Quantifying the dynamics of the oligomeric transcription factor STAT3 by pair correlation of molecular brightness - Elizabeth Hinde (Nature Portfolio, 2016)
Oligomerisation of transcription factors regulates their translocation into the nucleus, DNA binding affinity and sequence specificity. Here, Hinde et al. present a microscopy analysis, pair correlation of molecular brightness, that tracks the molecular mobility of different oligomeric species in the same cell.